2017
DOI: 10.3851/imp3215
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Zika Virus: Hurdles toward Vaccine Development and the Way Forward

Abstract: The Zika virus (ZIKV) epidemic has recently emerged as a public health threat due to its teratogenic nature and association with the serious neurological condition Guillain-Barré syndrome (GBS). To date, no approved antiviral therapeutics to treat, nor vaccines to prevent, ZIKV infection are available. In order to develop effective anti-ZIKV vaccines, improved animal models and a better understanding of immunological correlates of protection against ZIKV are required. In this paper, we discuss the recent progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Several studies reported varying viral load levels when comparing men and women; some reported women had higher load levels and some reported lower load levels compared to men, as well as studies reporting no difference in viral load level [ 56 58 ]. However, there seems to be support for an overall lower viral load level and COVID-19 outcomes for women, as the immune regulatory genes from the X chromosomes in women appear to cause lower viral load levels, inflammation and death after COVID-19 infections [ 57 , 59 ]. The differences in SexHs may have led to the found disparity between male and female residents.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported varying viral load levels when comparing men and women; some reported women had higher load levels and some reported lower load levels compared to men, as well as studies reporting no difference in viral load level [ 56 58 ]. However, there seems to be support for an overall lower viral load level and COVID-19 outcomes for women, as the immune regulatory genes from the X chromosomes in women appear to cause lower viral load levels, inflammation and death after COVID-19 infections [ 57 , 59 ]. The differences in SexHs may have led to the found disparity between male and female residents.…”
Section: Discussionmentioning
confidence: 99%
“…Zika virus (ZIKV) has emerged as a public health threat due to its teratogenic nature and associated with the occurrence of GBS ( 135 , 136 ). The mechanism of ZIKV infection causing GBS is unclear.…”
Section: Role Of Tlrs In Neuroimmune Diseasesmentioning
confidence: 99%
“…Zika virus (ZIKV) is a mosquito-borne flavivirus that is the focus of an ongoing pandemic and public health emergency and represents a public health threat due to its teratogenic nature causing microcephaly in babies born to infected mothers and association with the serious neurological condition Guillain-Barre syndrome in adults (Plourde and Bloch 2016). Haque et al (2018) proposed strategies to design effective and safe vaccines against ZIKV, including Toll-like receptors based NPs vaccines. The development of biomimetic nanodecoy (ND) that traps ZIKV and inhibits ZIKV infection was suggested by Rao et al (2019).…”
Section: Dengue Virus and Zika Virusmentioning
confidence: 99%